The Role of Servants of God in Holistic Mission Service in the Postmodern Era - Sambo, Ferdy (Jurnal Indonesia Sosial Sains, 2024)
The mission must be carried out, namely preaching the Word of God to the Ends of the Earth. The purpose of this research is to determine the role of God's servants in holistic mission service in the post-modern era. The research method the author uses is a descriptive qualitative method. Research subject: The Role of God's Servants in Holistic Mission Service in the post-modern Era. Research object: The Role of God's Servants in Holistic Mission Service. The data collection techniques used were observation, documentation and interviews. The research results found that the role of God's servants in Holistic Mission Service was increasing. in terms of quality and quantity.